Case Report: Vascular access in paediatric haemodialysis patients—creating and maintaining the patency of an arteriovenous fistula - Stroescu, Ramona; Comsa, Serban; Chisavu, Flavia; Gafencu, Mihai (Frontiers in Surgery, 2024)
Paediatric vascular access is a demanding field. The need for a multidisciplinary team is mandatory in children with end stage kidney disease. Central venous catheters (CVC) are still the first choice all over the world. Emerging data from the last several years showed the benefits in using arteriovenous fistulas (AVF) in the paediatric population for long term vascular access. The small vessel size in children represents a surgical challenge for vascular access.We report 3 cases from our haemodialysis department and the difficulty in maintaining a permanent vascular access. The first case is an adolescent girl that required a change in vascular approach after multiple CVC infections and catheter thrombosis secondary to thrombophilia. Three AVFs were performed but failure occurred early. The patient was also diagnosed with and a complex vascular thrombosis with total occlusion of the inferior vena cava and completes distal thrombosis of the superior vena cava. A permanent CVC was placed in the right jugular vein with the tip in the azygos vein. The second case is of an adolescent boy with systemic vasculitis with multiple CVCs infections secondary to immunosuppression. The first two right AVF's thrombosis occurred early with development of a pseudo aneurysm that required surgical intervention. The left brachial cephalic fistula required surgery for closing the collaterals, repositioning and superficialization. The third case is an adolescent with one surgical stage brachial-basilica left AVF and the difficulties in venous puncturing.Vascular access in pediatric hemodialysis remains a demanding field. There is a need of a multidisciplinary team -vascular surgeon as well as an interventional radiologist specialized in children.